• $V = a\cdot b\cdot c$
1 2
$a = \frac{ V}{b\cdot c}$
1 2
$b = \frac{ V}{a\cdot c}$
1 2
$c = \frac{ V}{b\cdot a}$
1 2
$O = 2\cdot (a\cdot b + a\cdot c + b\cdot c)$
1 2
$a = \frac{O-2\cdot b\cdot c}{2\cdot (b+c)}$
1 2
$b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}$
1 2
$c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)}$
1 2
$d = \sqrt{a^{2} +b^{2} +c^{2} }$
1 2
$a = \sqrt{d^{2} -b^{2} -c^{2} }$
1 2
$b = \sqrt{d^{2} -a^{2} -c^{2} }$
1 2
$c = \sqrt{d^{2} -b^{2} -a^{2} }$
1 2

Beispiel Nr: 02
$\text{Gegeben:}\\\text{Höhe} \qquad c \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}\\ \textbf{Gegeben:} \\ c=7m \qquad a=2m \qquad O=9m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)} \\ c=7m\\ a=2m\\ O=9m^{2}\\ b = \frac{9m^{2}-2\cdot 2m\cdot 7m}{2\cdot (2m+7m)}\\\\b=-1\frac{1}{18}m \\\\\\ \small \begin{array}{|l|} \hline c=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline a=\\ \hline 2 m \\ \hline 20 dm \\ \hline 200 cm \\ \hline 2\cdot 10^{3} mm \\ \hline 2\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline O=\\ \hline 9 m^2 \\ \hline 900 dm^2 \\ \hline 9\cdot 10^{4} cm^2 \\ \hline 9\cdot 10^{6} mm^2 \\ \hline \frac{9}{100} a \\ \hline 0,0009 ha \\ \hline \end{array} \small \begin{array}{|l|} \hline b=\\ \hline -1\frac{1}{18} m \\ \hline -10\frac{5}{9} dm \\ \hline -105\frac{5}{9} cm \\ \hline -1055\frac{5}{9} mm \\ \hline -1055555\frac{5}{9} \mu m \\ \hline \end{array}$